Overshoot Structure Near the Earth’s Subsolar Magnetopause Generated by Magnetopause Motions - Song, Xiaojian; Zuo, Pingbing; Shen, Zhenning; Feng, Xueshang; Xu, Xiaojun; Wang, Yi; Jiang, Chaowei; Luo, Xi (Frontiers in Physics, 2022)
For magnetopause crossing events, the observed magnetospheric magnetic fields in the vicinity of the subsolar magnetopause frequently present an overshoot structure; that is, in small vicinity of the magnetopause, the closer to the magnetopause, the stronger the magnetospheric magnetic field is. In this investigation, an automatic identification algorithm is developed to rapidly and effectively search the magnetopause crossing events using THEMIS data from 2007 to 2021. Nearly 59% of magnetopause crossing events identified near the subsolar region appear an overshoot structure. The statistical result shows that, for overshoot cases, the normalized change rate of magnetospheric magnetic field near the magnetopause is linearly related to the normalized magnetopause velocity, which means that the overshoot structure may be caused by the redistribution of the magnetospheric magnetic field due to the rapid magnetopause motion.